Innovation Ecosystem Catalysed by National Agricultural Innovation Project - Rao, D. Rama; Pandey, P. S.; Devakumar, C. (Indian Farming, 2015)
The National Agricultural Innovation Project (NAIP) was designed to investigate various innovative mechanisms as pilot studies through well drawn consortium architecture. Harnessing innovation can reduce costs, energy use and dudgery; enhance efficiency, and promote green agriculture.